A Noteon Debt Reduction and Echonomic Efficiency. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This note examines the efficiency gains that might result from market-based debt reduction and alternative uses of resources. It is argued that when a country's expected output falls short of contractual claims on that output, private investment is drawn to activities that protect the investors' share of future output at the expense of activities that increase future output. Resources provided by a third party could reduce this gap through market-based debt reduction or by supporting government investment or consumption. Given considerable uncertainty about the efficiency returns of alternative uses of resources, it seems likely that an optimal strategy would include both debt reduction and government investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt; Investment; Market; Return; WP